Model Konseptual Analisis Perbaikan Kinerja Industri Gula - Triwulandari S. Dewayana; M. Syamsul Ma’arif; Sukardi Sukardi; Sapta Raharja (JURNAL TEKNIK INDUSTRI, 2011)
Research related to the analysis of performance improvement (as used in a systematic process to identify performance, determine the desired performance targets, and to determine the priority of improvement at the sugar industry in Indonesia has not been done. This research aims to produce a conceptual model that can be used to analyze the sugar industry performance improvement. The model produced an integrated model to achieve the objectives of the analysis phase of performance improvement. The resulting model consists of five sub-models : 1) grouping, 2) performance measurement, 3) selection of the best performance, 4) analysis of best practices, and 5) determination of priorities for improvement.